2021
DOI: 10.1155/2021/3182745
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of Chronic Injured Distal Tibiofibular Syndesmosis with Autogenous Tendon Graft: A Systematic Review

Abstract: Background. Chronic injuries of the distal tibiofibular syndesmosis are common in patients who fail to receive adequate diagnosis and timely treatment. Reconstruction of the distal tibiofibular syndesmosis with an autogenous tendon graft in these patients is effective, although relatively rarely reported. Purpose. To investigate clinical outcomes of syndesmosis reconstruction with an autogenous tendon graft for chronic injuries of the distal tibiofibular syndesmosis by reviewing the current literature. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…Although they showed excellent outcomes in their series using gracilis autograft fixed with an interference screw, all six of their patients had surgery within 2 years after their first injury. Xu et al , in their systematic review, found that autograft reconstruction regains the micromotion at the joint, and most of the patients return to their work and sports 4. We believe all chronic syndesmotic injuries can be treated mainly by soft tissue reconstruction with or without a protective cortical screw 21.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Although they showed excellent outcomes in their series using gracilis autograft fixed with an interference screw, all six of their patients had surgery within 2 years after their first injury. Xu et al , in their systematic review, found that autograft reconstruction regains the micromotion at the joint, and most of the patients return to their work and sports 4. We believe all chronic syndesmotic injuries can be treated mainly by soft tissue reconstruction with or without a protective cortical screw 21.…”
Section: Discussionmentioning
confidence: 85%
“…Han et al , with the largest group of patients, compared the outcome of screw fixation and arthroscopic debridement versus arthroscopic debridement alone 5. They found no significant outcome between the two groups, claiming that the cause of pain is mainly due to the interposition of fibrous tissue rather than absolute mechanical instability 4. Yasui et al did a similar anatomical reconstruction of the anteroinferior tibiofibular ligament (AITFL) and arthroscopic debridement 1 20.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 Among the available surgical options for chronic injuries, tibiofibular stabilization and arthrodesis yield improved American Orthopaedic Foot & Ankle Society (AOFAS) scores. 5,8 Arthrodesis has been recommended for lesions with significant displacement, but the subsequently limited range of motion narrows its indication to nonactive patients. 5 In contrast, anteroinferior tibiofibular (AITFL) and interosseous ligament (IOL) reconstruction techniques with autografts can yield better functional results by preserving its physiologic joint micromotion.…”
Section: Introductionmentioning
confidence: 99%
“…5 In contrast, anteroinferior tibiofibular (AITFL) and interosseous ligament (IOL) reconstruction techniques with autografts can yield better functional results by preserving its physiologic joint micromotion. 8…”
Section: Introductionmentioning
confidence: 99%